2023
DOI: 10.1007/s00360-023-01499-0
|View full text |Cite
|
Sign up to set email alerts
|

Developmental, physiologic and phylogenetic perspectives on the expression and regulation of myosin heavy chains in mammalian skeletal muscles

Abstract: The kinetics of myosin controls the speed and power of muscle contraction. Mammalian skeletal muscles express twelve kinetically different myosin heavy chain (MyHC) genes which provides a wide range of muscle speeds to meet different functional demands. Myogenic progenitors from diverse craniofacial and somitic mesoderm specify muscle allotypes with different repertoires for MyHC expression. This review provides a brief synopsis on the historical and current views on how cell lineage, neural impulse patterns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 338 publications
0
4
0
Order By: Relevance
“…Additionally, we have observed that muscle hypertrophy in the non-immobilized leg mainly occurs in fast fibers. Compared to slow-twitch fibers, fast-twitch fibers have higher contractile and power output capabilities but are weaker in terms of endurance and fatigue resistance [ 52 ]. This means that fast-twitch fibers rely more on high-energy phosphates for energy supply and are more prone to degradation during long-term disuse and malnutrition periods.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have observed that muscle hypertrophy in the non-immobilized leg mainly occurs in fast fibers. Compared to slow-twitch fibers, fast-twitch fibers have higher contractile and power output capabilities but are weaker in terms of endurance and fatigue resistance [ 52 ]. This means that fast-twitch fibers rely more on high-energy phosphates for energy supply and are more prone to degradation during long-term disuse and malnutrition periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, during hypothyroidism in adult cats, fast fibres of fast primary origin revert to expressing β-slow MyHC, while fast fibres of fast secondary origin express 2A MyHC [208]. The 2B MyHC-expressing fibres in the mature animal derived from fast primary and fast secondary myotubes are not the same but constitute distinct ontotypes which retain their intrinsic myotube-derived properties in adult life: under hypothyroidism, only fibres derived from fast primaries express β-slow MyHC [129].…”
Section: Ontogeny Of Jaw-closing Muscles In Carnivoresmentioning
confidence: 97%
“…For example, we do not know the cellular and molecular basis of the division of EOMs into global and orbital layers, nor the basis for the variation in MyHC expression along the fibre length. In limb muscles, the postnatal surge of thyroid hormone [128] and the emergence of different neural impulse patterns play key roles in muscle fibre maturation [129]. While the role of the nerve is proposed below, there has apparently been no study of the possible role of thyroid hormone in postnatal MyHC expression in EOMs.…”
Section: Ontogeny Of Eomsmentioning
confidence: 99%
“…Myosin heavy chains (MyHC) of the types MyHC-1/beta ( MYH7 gene), MyHC-2a ( MYH2 gene), MyHC-2x ( MYH1 gene) and MyHC-2b ( MYH4 gene) are superb indicators of the main fiber types I, IIa, IIx and IIb, respectively [ 190 , 191 , 192 ]. Developing and specialized types of skeletal muscles are also associated with particular myosin isoforms, such as MyHC-embryonic ( MYH3 gene) and MyHC-neonatal ( MYH8 gene) during myogenesis [ 194 , 195 ] and MyHC-eom ( MYH13 gene) and MyHC-15 ( MYH15 gene) in extraocular muscles [ 196 , 197 ]. A detailed review has recently outlined myosin isoform diversity in the contractile apparatus of skeletal muscles [ 49 ].…”
Section: Skeletal Muscle Heterogeneity and Muscle Proteomicsmentioning
confidence: 99%